TRANSFORMASI PEMANFAATAN RUANG KOMUNAL PADA PERMUKIMAN TRADISIONAL BALI DI DESA PEKRAMAN PEDUNGAN - Ni Made Emmi Nutrisia Dewi (Universitas Udayana, 2014)
Abstract Communal spaces of Pedungan Village (Denpasar, Bali) have played important roles within the community. They have acted as places for various communal activities and interactions which over time have grown in type and scale. This takes place in line with level of physical and social development the Pedungan Village has been through. It is written based on a study aiming at how functions of these communal spaces have been transformed, as well as factors behind this transformation. The study achieves its objective by first, analysing the use/s of each communal space by certain groups within its communities and how these uses have changed. Second, it develops typologes of functional transformation experienced by many forms of communal spaces of Pedungan Village. In doing so, it implements qualitative research approaches and a naturalistic research paradigm. It is discovered that communal spaces have been transformed bith in functions and spatial structures. Major factors behind this transformation include systems of belief, customs and traditions, an increasing need for space, economic considerations, and the location of the communal space being studied. This study finds that the most functional transformations have taken place in communal spaces of a balai banjar. Such a trend however, does not happen on communal spaces where religious/ritual activities are performed. This is bcause ritual places are sacred and therefore cannot be amended, both in their uses and structures as is the case of other public spaces.Keywords: communal space, spatial use, spatial transformationAbstrak Ruang-ruang komunal telah memiliki peran yang penting dalam keseharian di Desa Pekraman Pedungan (Denpasar, Bali). Ruang-ruang ini telah menjadi wadah bagi masyarakat dalam beraktivitas dan berinteraksi, dan fungsi ini telah mengalami perkembangan baik secara tipe maupun skala dari waktu ke waktu. Artikel ini diulis berdasarkan sebuah studi yang bertujuan untuk menstudi bagaimana fungsi ruang-ruang komunal telah ditransformasi beserta faktor-faktor yang melandasinya. Dalam mencapai tujuannya, studi ini menerapkan pendekatan penelitian kualitatif dan paradigma naturalistik. Hasil studi menemukan bahwa ruang-ruang komunal di Desa Pedungan tidak hanya telah mengalami transformasi secara fungsi, namun juga secara struktur keruangan. Faktor utama yang mempengaruhi terjadinya transformasi termasuk sistem kepercayaan, tradisi dan adat istiadat, peningkatan kebutuhan akan ruang, pertimbangan ekonomi, dan lokasi dari site dimana ruang komunal tersebut berada. Lebih lanjut studi ini menemukan bahwa, ruang komunal yang paling banyak mengalami trasnformasi adalah ruang-ruang yang ada di balai banjar. Tetapi berbeda dengan balai banjar, ruang-ruang komunal di tempat-tempat berfungsi religius/ritual mengalami transformasi yang paling sedikit. Ini dikarenakan adanya pandangan akan ruang-ruang yang berada di sebuah tempat ritual bernilai sakral yang tidak bisa dirubah semudah mentransformasi ruang-ruang komunal lainnya. Kata kunci: ruang komunal, pemanfaatan ruang, transformasi ruang